Examining Financial Decision-Making of Retail Investors in Pakistan Stock Exchange (PSX): Moderating Role of Financial Literacy - Muhammad Rehman Shafique; Aamir Sohail; Shoaib Nisar; Munir , Muhammad (Journal of Applied Research and Multidisciplinary Studies, 2023)
This research aims to investigate the critical factors that affect the financial decision-making of retail investors in Pakistan Stock Exchange (PSX), with a focus on the moderating role of financial literacy. This information is crucial to understand the behavior of retail investors which can help financial institutions and market regulators to develop effective strategies to educate and guide investors. A quantitative research approach was employed to conduct this study. A sample of retail investors who invested in PSX was selected. Data was collected using a simple random sampling technique. After evaluating the missing values, 365 responses were considered for the final analysis. Smart-PLS was used for analyzing both the measurement model (used to analyze the validity and reliability of data) and the structural model (used to test the hypothesis). In the current study, a higher-order construct approach was adopted to evaluate the reflective-formative indicators of factors affecting the financial decision-making of retail investors. The results revealed that all exogenous variables have a significant influence on the financial decisions of retail investors in the PSX. As per the empirical findings, financial literacy moderates the relationship between exogenous and endogenous variables. The results would be useful for policymakers, financial regulators, and investment firms in designing effective financial education programs and investment products that meet the needs and preferences of retail investors in PSX.